Analisis Potensi dan Peluang Pengembangan Kakao Desa Sidomulyo, Kecamatan Lebakbarang, Kabupaten Pekalongan - Adicha Rahmawati; Edy Hartulistiyoso (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Institut Pertanian Bogor, 2020)
Cocoa production in Sidomulyo Village is reduced due to various factors including pest and disease attacks such as CPB and fruit rot, old plants, lack of maintenance and land use change with plants that are easier to maintain. The results of the SWOT analysis show that the potential and opportunities for increasing cocoa production in Sidomulyo Village are still very large. The production can be increased by doing intensification, that is improving the cultivation system, and also extensification, that is the expansion of the planting area. Intensification provides a great opportunity to increase productivity and crop production. The low production is due to the lack of farmer’s knowlegde about innovation in cultivatoon tech. The expansion of the area is still constrained by the polyculture system or intercropping between cocoa and other crops which are a source of secondary income. Through good application to innovation in cultivation and processing and the use of potential areas for expanding cocoa growing areas, it can be ensured that the productivity and production of cocoa in Sidomulyo Village can increase sharply. Increased cocoa production will increase farmer’s income and walfare, moreover it will also affect the regional economy. The purpose of this project is to analyze potential and development opportunity of cocoa in Sidomulyo village Lebakbarang district Pekalongan regency. Keywords: opportunity, potency of cocoa, productivity